MEMBACA TEKS/BUKU BERBAHASA INGGRIS BERSAMA ANAK-ANAK DI SMA NEGERI 1 ABEPURA JAYAPURA - Monika Gultom (LPPM Uncen, 2019)
The community service activity aims to be able to help improving the ability and English language skills of children at Abepura 1 Public High School, foster a love of reading English texts / books, and also to increase children's sense of enlightenment in reading texts or books. in English language. The specific purpose of the service activities for children at Abepura 1 High School introduces the folklore text from the Dani (Wamena) tribe that has been translated into English that is suitable for the age of the high school students, which are fun and interesting, so hopefully, the love of local culture in the form of Papuan folklore would also increase. The community service activities involved several students of English Language Education Study Program FKIP, who had participated in the KBA course (Middle / High School Curriculum and Teaching Materials), where this activity was also one form of application of the learned science and theory in the course. This community service activity was held for approximately one month including the selection of Dani folklores, deepening of folklore material, making media to deliver text to children, and explaining the participants students from English Language Education Study Program FKIP UNCEN about their understanding of folklore texts given through learning media he made before going to the field, surveying the location, implementation, and results seminar. This activity is useful for deepening the knowledge of English for children in SMA Negeri 1 Abepura, Jayapura, in understanding English texts through Dani folklores so that it will enhance both the sense of mind and confidence in reading English texts and love of stories people who have culture around their environment. The use of local folklore and the creation of media used to invite children to read while learning is a valuable field experience for prospective students of English teachers in the English Language Education Study Program FKIP UNCEN in applying their knowledge and knowledge.Keywords: Reading English Texts, Children, Papuan Folklore, Jayapura